Ectopic gut colonization: a metagenomic study of the oral and gut microbiome in Crohn’s disease - Hu, Shijia (Gut Pathog, 2021)
BACKGROUND: This study aims to characterize, the gut and oral microbiome in Asian subjects with Crohn’s disease (CD) using whole genome shotgun sequencing, thereby allowing for strain-level comparison. METHODS: A case–control study with age, sex and ethnicity matched healthy controls was conducted. CD subjects were limited to well-controlled patients without oral manifestations. Fecal and saliva samples were collected for characterization of gut and oral microbiome respectively. Microbial DNA were extracted, libraries prepared and sequenced reads profiled. Taxonomic diversity, taxonomic association, strain typing and microbial gene pathway analyses were conducted. RESULTS: The study recruited 25 subjects with CD and 25 healthy controls. The oral microbe Streptococcus salivarius was found to be enriched and of concordant strains in the gut and oral microbiome of Crohn’s disease subjects. This was more likely in CD subjects with higher Crohn’s Disease Activity Index (184.3 ± 2.9 vs 67.1 ± 82.5, p = 0.012) and active disease status (Diarrhoea/abdominal pain/blood-in-stool/fever and fatigue) (p = 0.016). Gut species found to be significantly depleted in CD compared to control (Relative abundance: Median[Range]) include: Faecalibacterium prausnitzii (0.03[0.00–4.56] vs 13.69[5.32–18.71], p = 0.010), Roseburia inulinivorans (0.00[0.00–0.03] vs 0.21[0.01–0.53], p = 0.010) and Alistipes senegalensis (0.00[0.00–0.00] vs 0.00[0.00–0.02], p = 0.029). While Clostridium nexile (0.00[0.00–0.12] vs 0.00[0.00–0.00], p = 0.038) and Ruminococcus gnavus (0.43[0.02–0.33] vs 0.00[0.00–0.13], p = 0.043) were found to be enriched. C. nexile enrichment was not found in CD subjects of European descent. Microbial arginine (Linear-discriminant-analysis: 3.162, p = 0.001) and isoprene (Linear-discriminant-analysis: 3.058, p < 0.001) pathways were found at a higher relative abundance level in gut microbiome of Crohn’s disease. CONCLUSIONS: There was evidence of ectopic gut colonization by oral bacteria, especially during the active phase of CD. Previously studied gut microbial differences were detected, in addition to novel associations which could have resulted from geographical/ethnic differences to subjects of European descent. Differences in microbial pathways provide possible targets for microbiome modification.